2019
DOI: 10.29252/qums.13.10.72
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Premenstrual Syndrome and Its Relationship with Psychological Well-Being in Students of Qom University of Medical Sciences, (Iran)

Abstract: Background and Objectives:Premenstrual syndrome is defined as a group of physical and psychological symptom, which happens during luteal phase of the menstrual cycle. Researches have indicated that premenstrual syndrome has significant effects on mental health and well-being of women. The purpose of the present study was to investigate the prevalence and severity of premenstrual syndrome and its relationship with psychological well-being in the students of Qom University of Medical Sciences. Methods:In this de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In this study, moderate–severe PMS and PMDD prevalence were 33.9% and 12.3%, respectively. On the other hand, previous studies have reported the prevalence of moderate–severe PMS and PMDD from 25.1%–49.8% and 4.3%–44.5%, respectively 10–15 . Due to the high prevalence of moderate–severe PMS and its adverse effects on human life, 4–7 early diagnosis and treatment are of great importance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, moderate–severe PMS and PMDD prevalence were 33.9% and 12.3%, respectively. On the other hand, previous studies have reported the prevalence of moderate–severe PMS and PMDD from 25.1%–49.8% and 4.3%–44.5%, respectively 10–15 . Due to the high prevalence of moderate–severe PMS and its adverse effects on human life, 4–7 early diagnosis and treatment are of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, previous studies have reported the prevalence of moderate-severe PMS and PMDD from 25.1%-49.8% and 4.3%-44.5%, respectively. [10][11][12][13][14][15] Due to the high prevalence of moderate-severe PMS and its adverse effects on human life, [4][5][6][7] early diagnosis and treatment are of great importance. Considering the differences in the results of published reports, [10][11][12][13][14][15] the findings of this study, along with other studies, necessitate conducting a meta-analysis in this field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since health disorders affect mental health and, on the other hand, the prevalence of mood disorders is higher in women, women with this syndrome are more prone to physical and mental disorders [2,15,16]. According to a study, there was a significant relationship between psychological well-being and the severity of PMS symptoms among female students [17]. Therefore, it is necessary to consider strategies to improve mental health and marital satisfaction in women with PMS.…”
Section: Introductionmentioning
confidence: 99%